Monocular Presentation Attenuates Change Blindness During the Use of Augmented Reality - Kitamura, Akihiko; Kinosada, Yasunori; Shinohara, Kazumitsu (Frontiers in Psychology, 2019)
Augmented reality (AR) is an emerging technology in which information is superimposed onto the real world directly in front of observers. AR images may behave as distractors because they are inside the observer’s field of view and may cause observers to overlook important information in the real world. This kind of overlooking of events or objects is known as “change blindness.” In change blindness, a distractor may cause someone to overlook a change between an original image and a modified image. In the present study, we investigated whether change blindness occurs when AR is used and whether the AR presentation method influences change blindness. An AR image was presented binocularly or monocularly as a distractor in a typical flicker paradigm. In the binocular presentation, the AR image was presented to the both of the participants’ eyes, so, it was not different from the typical flicker paradigm. In contrast, in the monocular presentation, the AR image was presented to only one eye. Therefore, it was hypothesized that if participants could observe the real-world image through the eye to which the AR image was not presented, change blindness would be avoided because the moment of change itself could be observed. In addition, the luminance of the AR image was expected to influence the ease to observe the real world because the AR image is somewhat translucent. Hence, the AR distractor had three luminance conditions (high, medium, low), and we compared how many alternations were needed to detect changes among the conditions. Result revealed that more alternations were needed in the binocular presentation and in the high luminance condition. However, in all luminance conditions in the monocular presentation, the number of alternations needed to detect the change was not significantly different from that when the AR distractor was not presented. This result indicates that the monocular presentation could attenuate change blindness, and this might be because the observers’ visual attention is attracted to the location where the change has occurred automatically.